Perspectives on exercise participation among Canadian university students. (November 2019) - Silver, Michelle Pannor; Easty, Laura Kathleen; Sewell, Karen M.; Georges, Rosemary; Behman, Amy
Objective: University has been identified as an important time to develop exercise habits. The aim of this study was to examine factors that enhanced exercise participation among a diverse set of undergraduate students and their perceived facilitators as well as barriers to exercising regularly. Setting: A large public university in one of the largest and most ethno-culturally diverse regions of Canada. Method: A mixed-methods design was employed to examine factors associated with regular exercise participation among diverse Canadian undergraduate students ( N = 477). Survey data were analysed using logistic regression analyses to predict regular exercise participation. In addition, six focus group sessions explored barriers and facilitators to regular engagement in exercise ( n = 41). Results: Survey findings indicated that being male, having a parent that attended college, and religious affiliation were predictive of exercising regularly. Thematic analysis of qualitative findings highlighted the complex roles that religion, intimidation, peer support and priority-setting played in college students' exercise participation. Conclusion: Findings can inform ongoing strategies to promote exercise participation in early adulthood, particularly among diverse college students.